The impact of being bullied at school on psychological distress and work engagement in a community sample of adult workers in Japan - Iwanaga, Mai (PLoS One, 2018)
OBJECTIVE: The aim of this study was to investigate the long-term impact of being bullied at school on current psychological distress and work engagement in adulthood among Japanese workers. We hypothesized that workers who had been bullied at school could have higher psychological distress and lower work engagement compared to those who had not been bullied. METHODS: We used data from the Japanese Study on Stratification, Health, Income, and Neighborhood (J-SHINE) project, conducted from July 2010 to February 2011 in Japan. This survey randomly selected the local residents around a metropolitan area in Japan. Of 13,920 adults originally selected, 4,317 people participated this survey, and the total response rate was 31%. The self-administered questionnaires assessed current psychological distress (K6), work engagement (UWES), the experiences of being bullied in elementary or junior high school and other covariates. Statistical analyses were conducted only for workers. Hierarchical multiple regression analyses were conducted to determine associations between experiences of being bullied at school and psychological distress/work engagement, with six steps. RESULT: Statistical analysis was conducted for 3,111 workers. The number of respondents who reported being bullied in elementary or junior high school was 1,318 (42%). We found that the experience of being bullied at school was significantly associated with high psychological distress in adulthood (β = .079, p = < .0001); however, the work engagement scores of respondents who were bullied were significantly higher than for people who were not bullied at school (β = .068, p = < .0001), after adjusting all covariates. CONCLUSION: Being bullied at school was positively associated with both psychological distress and work engagement in a sample of workers. Being bullied at school may be a predisposing factor for psychological distress, as previously reported. The higher levels of work engagement among people who experienced being bullied at school may be because some of them might have overcome the experience to gain more psychological resilience.